Integrating Quality Function Deployment and Service Excellence for Educational Quality Enhancement in Higher Education - Lukman, Lukman; Vegatama, Meita Rezki (JURNAL AL-TANZIM, 2023)
This article aims to analyze the integration of quality function deployment (QFD) and excellent service in improving the quality of education at STT Migas Balikpapan. This research uses a qualitative case study type approach. Data collection techniques are carried out through observation, interviews, and documentation. Data analysis is carried out circularly, starting with data collection, presentation, reduction, and conclusion. The results of this research show that integration of quality function deployment (QFD) and service excellence in order to improve the quality of education at STT Migas Balikpapan is carried out through the identification of customer needs, the transformation of needs into action plans, alignment with superior service, continuous measurement, and evaluation. The results of this research can provide practical guidance for higher education institutions in improving the quality of their education in a way that is more focused, responsive, and oriented to the needs of students and industry. It is hoped that integrating QFD and excellent service can become the basis for educational renewal in similar universities.